1981
DOI: 10.1113/jphysiol.1981.sp013772
|View full text |Cite
|
Sign up to set email alerts
|

Changes in activity of vagal bronchopulmonary C fibres by chemical and physical stimuli in the cat.

Abstract: SUMMARY1. In eighteen anaesthetized cats, action potentials in non-myelinated vagal afferent neurones were recorded in the nodose ganglion by means of extracellular micro-electrodes.2. The pulmonary or bronchial origin of these C fibres was assessed in closed chest preparations by injecting phenyl diguanide into either the right atrium or the ascending aorta (bronchial circulation). This was confirmed in two animals by local mechanical stimulation.3. Eighty per cent of bronchopulmonary C fibres increased their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 21 publications
3
22
0
Order By: Relevance
“…On the basis of response latency, they further postulated that these "CO 2 sensors" are located between alveoli and capillaries. A paradoxical stimulatory effect of CO 2 on pulmonary C fibers was reported in cats by Delpierre et al (6), but the locations of most of the receptors were not identified in the lung in their study. In comparison, our study showed a much smaller percentage of pulmonary C fibers exhibiting CO 2 sensitivity in rats under normal conditions.…”
Section: Discussionmentioning
confidence: 52%
“…On the basis of response latency, they further postulated that these "CO 2 sensors" are located between alveoli and capillaries. A paradoxical stimulatory effect of CO 2 on pulmonary C fibers was reported in cats by Delpierre et al (6), but the locations of most of the receptors were not identified in the lung in their study. In comparison, our study showed a much smaller percentage of pulmonary C fibers exhibiting CO 2 sensitivity in rats under normal conditions.…”
Section: Discussionmentioning
confidence: 52%
“…Animal studies however have not revealed this response but this could be because in all instances the animals were anaesthetized and in some the animals were given morphine and/or intubated via the trachea. In animals C-fibre stimulation leads to bronchoconstriction (Russell & Lai-Fook, 1979;Delpierre et al, 1981;Coleridge et al, 1982). This does not appear to be the response in man.…”
Section: Effect Ofsodium Cromoglycate On Capsaicin-induced Coughmentioning
confidence: 99%
“…It might be that to cause bronchoconstriction C-fibres sited lower in the airways need to be stimulated and that in the present study these were protected from exposure by the laryngeal 'guard'. The experimental design of the animal studies (Delpierre et al, 1981;Coleridge etal., 1982;1983) would have tended to direct the capsaicin to sites in the lower airways.…”
Section: Effect Ofsodium Cromoglycate On Capsaicin-induced Coughmentioning
confidence: 99%
“…Trenchard et al (1984) have recently suggested than nonmyelinated vagal lung receptors are sensitive to CO 2 and exhibit reflex effects on respiration in rabbits. Similar receptors have been identified in the cat (Delpierre et al, 1981) and the dog (Banzett et al, 1978; Downloaded by [University of Illinois at Urbana-Champaign] at 18:17 16 March 2015 Russell et al, 1984). Unequivocal establishment of this CO 2 sensitive receptor in mammalian lungs would provide the 'CO 2 flow hypothesis' with a solid foundation.…”
Section: Control Of Hyperpnoea By Comentioning
confidence: 64%